A study on the concept of rent and key factors affecting its occurrence in urban management in Iran (Case study of Tabriz Municipality) - Akbar Asghari Zamani; Shahrivar Rostaei; Hojjat Mohamadi Torkamani (نشریه جغرافیا و برنامه‌ریزی, 2022)
IntroductionPlanning as a regulatory process between public and private goals, as a result of the actions of individuals and groups deviates from its regulatory path and acts in a specific direction. This competition, influenced by power, has its own manifestation in the urban environment.The urban revolution and the consideration of the city as a spatial object, according to Lefebvre, put this socio-economic entity on a path that was increasingly attacked by capitalism, and the reproduction of artificial spaces for the accumulation of capital intensified.This reproduction is done in a set of rules and regulations and management policies that should, in fact, allocate space for public use, While the objective function of this city management organization has collapsed in favor of capital. This point has its own conditions in cities with rentier system. This is because in rentier systems, decentralization policies and, consequently, the strengthening of local institutions and urban management, in the absence of democratic conditions, have created a suitable environment for creating various types of rents and sometimes corruption.When urban space is considered as a commodity for possession, in this process urban management has its own impact. Sometimes as a law enforcement officer and sometimes as a competitor with private capital over urban space. All of this can be described as rent-seeking, in which individuals and groups try to divert resources to their advantage. All of these influences and everything that happens in the urban space are based on factors and contexts that seem to be rooted in the rentier political economy that governs the city system. Therefore, the present study tries to identify and explain the effective factors and contexts.Materials and methodsThe present study can be considered as applied in terms of purpose, although it has also been developed and theoretically explained. Also, the approach is descriptive-analytical, which based on the data obtained from documentary studies, as well as conducting interviews and using a questionnaire, has analyzed the context of rent in Tabriz Municipality.For conducting interviews, open-ended questions have been designed and presented to a number of managers and experts in the field of urban management in the metropolis of Tabriz.The results, after theoretical saturation and combination with the results of documentary studies, are extracted in the form of propositions and form the basis of a questionnaire that is left to the judgment of elites and experts to determine the importance and degree of effectiveness of each criterion in the occurrence of rent and rent-seeking phenomenon. For this purpose, the Mick Mac questionnaire was used. This method is based on the analysis of interaction / structural effects.Results and discussionThe requirement for analyzing variables using Mick Mac software is to determine their interactions in the form of an effect matrix that acts as software input. To do this, a 39 * 39 matrix was set and the relationships between the variables in terms of effectiveness were determined based on the opinions of selected experts in a purposeful sampling way. The number of repetitions considered in the software is twice and the degree of filling is 68.63%. This indicates that they have affected each other in more than 68% of cases. Out of 1269 relationships that can be evaluated in the matrix, 580 cases were unrelated (number zero), 379 cases were weak relationship (number one), 585 cases were moderate relationship (number two) and 305 cases were strong relationship (number three). The pattern of distribution of research variables indicates that the system is unstable.The distribution model shows that macroeconomic factors of political economy generally have high impact and low impressible, and in contrast, the factors that are most impressible are the result of decisions and macro-political and economic environment.Such a situation indicates the power of external and extra-organizational factors to determine the status of the system. impressible factors or results are also factors that are affected by the macro-political environment and political economy and operate mostly at the organizational and local level, in other words, they are the output of the performance of macro-decisions and events.In the structural / interaction analysis matrix, the sum of the row numbers for each variable indicates the effect of the variable and the sum of the columns of each variable indicates its Impressive. According to the matrix results, the variables related to the "political economy factor" have the most impact on the system (the occurrence of the rent phenomenon) and the variables related to the "psychological factor" have the least impact.Also in terms of impressiveness, the variables related to "organizational factor" have the most impressiveness and the variables related to "legal factor" have the least. Based on the results of direct and indirect effects, the variable of power centers has the highest score. Also, all the identified key variables from rank one to 16 are repeated in direct and indirect impact, and the differences are only in their rank.ConclusionThe present study seeks to identify and explain the factors affecting the formation of the phenomenon of rent and rent-seeking in the urban management organization. For this purpose, while conducting interviews with experts and managers related to urban management, first, 39 variables under 7 factors of political, political, economic, legal, organizational, socio-cultural and psychological economics were extracted.In the next step, using a questionnaire, the effectiveness of these variables was determined using the interaction / structural impact analysis method. In the next step, Mick Mac software was used to identify how the variables affect each other and identify key factors. The results of the software output can be summarized as follows;- Based on the pattern of distribution of variables, the system has an unstable state and the types of variables - influential, impressive, independent, regulatory and two-dimensional - can be identified in it.- The most effective is related to the variables of "political economy" and the least effective is related to the variables of "psychological".- In terms of impressiveness, the most impressiveness is related to "organizational" factor variables and the lowest impressiveness is related to "legal" factor variables. The key variables resulting from direct and indirect effects are identified as 16 variables, all of which are fixed and the differences are only related to their rank. These variables include;Centers of power, oil economy, lack of transparency, Clientelism policy, centralism, establishment of rentier state, weakness of popular institutions, government tenure, political influence, electoral assistance, desirability of rent-seeking among social groups, golden signatures, lobbying, the prevailing spirit of rent-seeking, the rule of the technocratic tradition among managers and the legal cases underlying rent.- Variables related to political economy are generally variables that have macro dimensions and in most cases are beyond the control of the local level of urban management. Local level variables are generally related to organizational factors that are generally the result of the performance of macro factors such as political economy. On the other hand, the variables related to political economy can be described as contextual variables that use their micro-organizational variables as tools to make their impact operational.